The Influence of Auditor Integrity, Competency and Professionalism on Internal Audit Quality - Syahdilla Aulia Rahman; Cris Kuntadi (Jurnal Stagflasi : Ekonomi, Manajemen dan Akuntansi, 2024)
Audit quality is very important for every company. High audit quality can increase a company's credibility. Audit quality itself is the result of the auditor's performance in carrying out the tasks concerned. This article discusses the factors that influence Internal Audit Quality, namely Integrity, Competence and Professionalism of Auditors. The purpose of writing this article is to examine the hypothesis of how auditor integrity, competence and professionalism influence audit quality. The results of this literature review are: 1) Integrity influences Internal Audit Quality; 2) Competency influences Internal Audit Quality; and 3) Auditor professionalism influences Internal Audit Quality.